Derivational Potential, or Word-Formation Possibilities of a Word: Problem of Defining the Term - E. V. Vasilyeva (Научный диалог)
The article is devoted to the understanding of the term derivational potential of a word or word-formation possibilities of a lexical unit . The relevance of the study is determined by the fact that the authors of modern works on derivatology do not always draw the reader’s attention to the difference between such concepts as derivational potential and implemented derivational potential , especially in the cases of description of constraints on the implementation of derivational potential. With the aim of identifying variants of interpretation of the term in the article a review of the research is made, the authors of which pay attention to the derivational features of words and problems of realization of these possibilities. The results of the analysis of scientific works indicate that there can be several interpretations of the term word-formation possibilities . Some researchers understand derivational potential as possibility of a specific word to form lexical units, others - as a set of word-formation possibilities that characterize a particular class of words. It is assumed that the reason for different understanding of derivational potential is that there are two ways to interpret the composition of the derivational paradigms of the lexical units in determining word-formation possibilities of producing word. The author, basing on the previous experience of researchers, formulates an elaborated definition of the term derivational potential .